Development of PMRI-Based LKPD in the Context of Lubuklinggau Local Wisdom on Pythagorean Theorem Material - Ratna Dewi Sari; Anna Fauziah; Lucy Asri Purwasi (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
The purpose of this research is to create a valid, useful, and potentially beneficial student worksheet for class VIII students that utilizes the material of the Pythagorean theorem in the context of Lubuklinggau local wisdom and Indonesian realistic mathematics education. The 4-D development paradigm, which comprises of the stages of define, design, develop, and disseminate, is being used in this development research project. This study involves class VIII students, math teachers, and validators (linguists, media specialists, and material experts). Techniques for gathering data include tests, questionnaires, observations, and interviews. The generated LKPD has a language validity of 0.78 in the valid category, media validity of 0.83 in the very valid category, and material validity of 0.81 in the very valid category based on the research findings. Based on these data, the mathematics worksheet developed in this research using Pythagorean theorem material in the context of local wisdom in the city of Lubuk-Lingau is very valid and practical and has potential effects so that it can be used to study the Pythagorean theorem.